2018
DOI: 10.1016/j.jenvman.2018.07.098
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive spatial-temporal analysis of driving factors of human-caused wildfires in Spain using Geographically Weighted Logistic Regression

Abstract: Over the last decades, authorities responsible on forest fire have encouraged research on fire triggering factors, recognizing this as a critical point to achieve a greater understanding of fire occurrence patterns and improve preventive measures. The key objectives of this study are to investigate and analyze spatial-temporal changes in the contribution of wildfire drivers in Spain, and provide deeper insights into the influence of fire features: cause, season and size. We explored several subsets of fire occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 73 publications
1
33
0
1
Order By: Relevance
“…Typically, only global-level statistical approaches were applied, under the assumption that relationships between explanatory factors and dependent variables are constant (homogenous) over space [24]. However, many socioeconomic drivers are known to exhibit spatial non-stationarity and to have distinct temporal signatures [25,26]. Brunsdon et al (1996) proposed Geographically Weighted Regression (GWR) as a method to explore spatial heterogeneity [27].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, only global-level statistical approaches were applied, under the assumption that relationships between explanatory factors and dependent variables are constant (homogenous) over space [24]. However, many socioeconomic drivers are known to exhibit spatial non-stationarity and to have distinct temporal signatures [25,26]. Brunsdon et al (1996) proposed Geographically Weighted Regression (GWR) as a method to explore spatial heterogeneity [27].…”
Section: Introductionmentioning
confidence: 99%
“…Those trends might be explained by the anomalies in the trajectory of the North Atlantic Jet [101], which could be related to a decrease of the cloudy atmosphere or which could provoke more severe droughts in some critical months of the year for the growth of vegetation. Other factors could be land degradation and insect plagues, in addition to the high rates of land abandonment and fragmentation, severe overgrazing, and the increase in wildfire occurrence in recent decades [109][110][111]. Furthermore, in this area, other studies suggest that the Fagus sylvatica species in the northern zones of Spain are less resistant to climate change than those located in the southern regions of Spain [112].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, anomalies in the trajectory of the North Atlantic jet stream [109] were found that could be related to a decrease in the cloudy atmosphere or that could provoke more severe droughts in some critical months of the year for the growth of vegetation. Other authors have reported that Cordillera Cantábrica suffered a land degradation with high rates of land abandoned and fragmented, a severe overgrazing, and an increase in wildfire occurrence during the past few decades [110][111][112]. Other studies suggest that the Fagus sylvatica species in northern zones of Spain is less resistant to climatic change than those located in southern areas of Spain [113].…”
Section: Discussionmentioning
confidence: 99%